The Impact of Trade Deficit in Nepalese Economy - Ashmita Dahal Chhetri (Journal of Balkumari College, 2022)
The objective of this paper is to study and analyze the growth and direction of Nepalese foreign trade along with the causes and recommendations of trade deficit. Efforts have been made to sort out the principal sources of the trade deficit in Nepal. Landlockedness, political instability, lack of export diversification, devaluation of domestic currency, lack of resources, etc. are the major causes of the trade deficit in Nepal. Nepal, being not self-reliant on factors of production, consumer goods and capital goods, needs to import goods from abroad. On another hand, Nepal’s exports are heavily concentrated; both in terms of product and destination. Nepal’s major trading partners are India, China, U.A.E, etc. During the year 2019/20, Nepal exports goods worth RS. 97.71 Billion And import goods worth RS. 1196.80 billion Leading to a trade deficit of Rs.1099.09 Billion. Trade deficit is acting as negative catalyst in the economic growth and GDP of a country. Increased deficit has caused suppressed inflation. Import to export ratio is continuously increasing as demand is increasing and these demands could not be met by the domestic producers. During the year 2019/20, the contribution of trade on GDP of Nepal is 40.65%. No doubt, trade is an engine of economic growth. So, after analyzing barriers in the foreign trade, some of the steps to be taken are recommended which includes the development of competitive ability and enhancement of Human Resources, commodity and market diversification, formulation of strong legal framework and trade policy, incentives for the promotion of export and priority in the agricultural and hydropower sectors.